Vāmana Malhāra Jośī, vyakti āṇi vicāra - Khāṇḍekara, Vi. Sa. (Vishṇu Sakhārāma), 1898-1976 (SAMP early 20th-century Indian books project ;)
On the life and works of Vāmana Malhāra Jośī, 1882-1943, Marathi author; contributed articles.